Current conditions and future projections of the e-book market in the Republic of Croatia - an overview of strengths, weaknesses, opportunities and threats (Libellarium: journal for research in the field of information and related sciences, 2023)
Objective. Taking into account the changes that have affected the publishing industry due to the rapid development of information and communication technologies, the aim of the paper is to analyze the development of electronic books (e-books) and electronic publishing (e-publishing) through a historical and theoretical perspective, giving indications of future development in the Republic of Croatia. Considering many advantages and disadvantages of e-books, but also available opportunities and potential threats, the paper aims to unify all the mentioned aspects in one place with the goal of systematizing the available scientific literature. The paper is, therefore, valuable to publishers and authors who have not yet recognized all the possibilities offered by e-books or do not fully understand all their functionalities.Approach/methodology/design. Methods of analysis, synthesis and comparison are applied to provide a detailed assessment of the strengths, weaknesses, opportunities, and threats (SWOT analysis) of the e-book as a product of electronic publishing. Through a systematic analysis of scientific and professional literature, the positive and negative aspects of e-books are elaborated on, new trends are discussed and indications are given of the future development of e-books with additional implications for e-publishing.Results. The “SWOT” analysis results demonstrate that electronic book has numerous advantages such as interactivity and functionality, and can be an efficient medium for information and knowledge transfer. On the other hand, the dependence on technology is its greatest weakness. New opportunities lie in new collaborations and new distribution channels, while the largest threat is the competition that can come from all over the world through digital channels.Originality/ value. This is the first paper outlining an overview of the strengths, weaknesses, opportunities and threats to e-books, thus allowing a better insight into the e-book market in Croatia.
Keywords: electronic book; electronic publishing; electronic readers; information and communication technologies; SWOT analysis